Síntese e caracterização de hidroxiapatita porosa com propriedades osteoativas - Freitas, Lucas Augusto de (2020)
Hydroxyapatite (PAH) is a calcium phosphate-based compound that can be extracted from animal bone tissue or synthesized. Due to its biocompatibility and bioactivity properties, it has a notorious application in the areas of implants and bone grafting. However, PAH has disadvantages regarding the dissemination of young cells, due to its low porosity. Thus, the present work aims to synthesize PAH with different pore builders (organic molecules such as PEC 1500, PVA and CMC) using mixing processes during the synthesis process (in situ) or mixed after the synthesized PAH (ex situ). The development aims at a biomaterial with better osteoconductive characteristics. In addition to this, the drug zoledronic acid will also be added to improve the process of cellular osteoactivation. The first results after the sintering process indicated that the best pore builder was the PEG1500 molecule through an in situ process (SEM test), generating a material with several pores with an average size of 1000 nm. The use of spray drying was adopted to better standardize the size of the HAP grain with a 1200 mm tip. The porosimetry tests indicated the predominant existence of intergranular voids and small pores. The cytotoxicity tests confirmed that the substance Zoledronic Acid is highly toxic in high concentrations and the ideal concentration should be sought.